Dynamic Control of Climbing Lane on Expressways - Ko, Hangeom; Han, Eum; Kim, Kyung Hyun; Park, Sangmin; Yun, Ilsoo (KSCE Journal of Civil Engineering, 2019)
Travel time on an expressway segment with a climbing lane may be affected by the appearance of slow-moving vehicles such as trucks. If slow-moving vehicles do not use the climbing lane, the traffic stream on the segment may worsen. In addition, forced lane changes to avoid such slow-moving vehicles lead to a significant threat of traffic accidents. The efficient operation of climbing lanes in terms of mobility and safety is one of the challenges faced by traffic engineers. The Korea Expressway Corporation suspends the operation of climbing lanes in an attempt to improve mobility and safety during high traffic demand periods such as national holidays and vacation seasons. Against this background, a methodology for the dynamic control of climbing lane operations based on realtime traffic conditions was developed in this research. The proposed method was evaluated using Vissim. The simulation results showed that the dynamic control of a climbing lane based on real-time traffic status improved mobility and safety by increasing the average travel speed by up to 15.6% and reducing the average delay and number of conflicts at the merging segment by up to 30.6% and 62.1%, respectively.
Keywords: Climbing lanes; closure; Dynamic controls; expressway; simulation; climbing lane; closure; dynamic control; expressway; simulation